A cohort study following up on a randomised controlled trial of a telemedicine application in COPD patients. (October 2015) - Dyrvig, Anne-Kirstine; Gerke, Oke; Kidholm, Kristian; Vondeling, Hindrik
Introduction: The studies that constitute the knowledge base of evidence based medicine represent only 5%–50% of patients seen in routine clinical practice. Therefore, whether the available evidence applies to the implementation of a particular service often remains unclear. Chronic obstructive pulmonary disease (COPD) is no exception. Methods: In this article, the effects of implementing a telemedicine intervention for COPD patients were analysed using data collected before, during, and after a randomised controlled trial (RCT). More specifically, regression techniques using robust variance estimators were used to analyse whether the use of telemedicine, patient age, and gender could explain the risk of readmission, length of hospital admission, and death during a five-year observation period. Results: Increased risk of readmission was significantly related to both use of telemedicine and increased age in three sub-periods of the study, whereas women showed a more pronounced risk of readmission than men only during and after the RCT period. The number of days admitted to hospital was higher for patients using telemedicine and being of older age. Risk of death during the observation period was decreased for patients using telemedicine and for female patients and increased for elderly patients. No interaction between intervention and time period was observed. Statistically significant relationships were identified between use of telemedicine and risk of readmission, days admitted to hospital, and death. Discussion: Research on effect modification in telemedicine is essential in designing future implementation of interventions as it cannot be taken for granted that effectiveness follows from efficacy.